Life Histories and Dynamic Objects: The Klasies River Mouth Collection. (April 2014) - Pyne, Lydia
Abstract Klasies River Mouth, a Middle Stone Age archaeological site along the southern coast of South Africa, has long held an iconic status within the field of archaeology, for many reasons. In the four decades since its original excavation, the site's artifact collection has demonstrated dynamic characteristics as the artifacts are analyzed, interpreted, and reinterpreted. The site and its collection became a standard (both scientifically and culturally) for comparing other Middle Stone Age sites. The collection, however, does more than just provide a comparative sample for archaeologists. The collection is a way to trace identity and shifting methodological and theoretical paradigms for Pleistocene archaeology. The life history of Klasies River Mouth pairs the physical materiality of the collection with its subsequent cultural (and disciplinary) cachet.